Advancements in Pancreatic Cancer Treatment: A Comprehensive Review of Current Therapies and Future Directions - Stec, Weronika Maria; Kudas, Zuzanna; Górka, Mateusz; Wojtkiewicz, Anna; Piekarska, Magda; Szerej, Krzysztof (Quality in Sport, 2024)
Pancreatic cancer still has a 5-year survival rate in the single digits, making it one of the most aggressive and deadly cancers. The therapy of pancreatic cancer presents considerable hurdles because of its late diagnosis, fast development, and resistance to traditional therapies, even with advancements in oncological research. This study offers a thorough summary of the various treatment options available today, including as radiation therapy, chemotherapy, surgery, and the newly recognized roles of immunotherapy and targeted medicines. We examine the most recent advancements in personalized medicine and molecular profiling, which are starting to challenge established therapy paradigms and provide fresh hope for bettering patient outcomes. The study also outlines ongoing clinical trials that attempt to address the shortcomings of current therapy, such as the toxicity and limited efficacy of chemotherapeutic drugs. This study aims to provide a comprehensive overview of the pancreatic cancer therapy landscape by analyzing both conventional and cutting-edge treatments. It also identifies promising directions for future research and clinical practice.